DISCOVERY OF RAPID OSCILLATIONS IN Ар STAR HD 99563 - Dorokhova, T. N. (Одеські астрономічні публікації, 2017)
The observations of roAp stars at the Mt. Dushak-Erekdag station of Odessa Astronomical Observatory (Central Asia) have been carried out since 1992. In 1994 the searches for a new roAp stars were initiated. There were investigated 5 stars - candidates: HD15257, HD17317, HD99563, HD115606, HD217401. Their photometric features are presented. The Fourier spectra of 4 stars did not show variability in the high frequency region. The Fourier spectrum of HD99563 revealed the oscillations with a period of about 11.2 min. and amplitude 3.98 mmag. Evidently HD99563 is a new discovered roAp star.